2019
DOI: 10.1111/cge.13628
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive role of DNA mismatch repair status in stage II‐III colorectal cancer: A systematic review and meta‐analysis

Abstract: DNA mismatch repair (MMR) status was considered to be a potential prognostic factor for colorectal cancer (CRC) but with conflicting reports, and varied in terms of TNM stages. Its relationship with prognosis in stage II-III CRC had not yet been systematically established. Therefore, we retrieved eligible studies published through May 2019, and screened out 51 studies that reported survival data (overall survival [OS] and/or disease-free survival [DFS]) in 28 331 CRC patients at stage II-III, totally 16.4% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“… 33 This finding has implications for daily clinical practice in relation to three important issues: prognosis, treatment and surveillance. In (early stage) colorectal cancer, MMR deficiency has been linked to a better prognosis, 25 34 35 an association that may also hold true for MMR-deficient small bowel cancers. Indeed, the aforementioned study by Aparicio et al reported a trend towards better prognosis for Lynch-associated small bowel adenocarcinomas versus those related to Crohn’s disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 33 This finding has implications for daily clinical practice in relation to three important issues: prognosis, treatment and surveillance. In (early stage) colorectal cancer, MMR deficiency has been linked to a better prognosis, 25 34 35 an association that may also hold true for MMR-deficient small bowel cancers. Indeed, the aforementioned study by Aparicio et al reported a trend towards better prognosis for Lynch-associated small bowel adenocarcinomas versus those related to Crohn’s disease.…”
Section: Discussionmentioning
confidence: 97%
“…Of particular note, the prevalence of MMR deficiency in our study differed considerably between the resected and biopsied specimens. A higher prevalence of MMR deficiency in resected versus biopsied samples might be related to the association of MMR deficiency with a better prognosis in other cancers, 25 so resections may represent patients with cancer with a relatively good prognosis, whereas biopsies may represent patients with a poor prognosis who are less likely to undergo resection. Interestingly, the prevalence of MMR deficiency identified in biopsied samples, 4.4%, is close to the 5.0% prevalence identified in a metastatic colorectal cancer cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Higher MRS was found in patients in cluster-B, and in those with advanced TNM stages, the C4C6 subtype, proximal colon cancer, and pMMR status (all P values < 0.05, Fig. 5 b–i), which have been previously confirmed to have a poor prognosis [ 18 , 31 , 32 ]. No significant difference in MRS were found for BRAF status, KRAS status, TP53 status, sex, CIN status, or CIMP status (Additional file 12 : Figure S5a–f).…”
Section: Resultsmentioning
confidence: 67%
“…Overall, 153 patients received adjuvant chemotherapy with mFOLOFX6 after surgery, which consisted of 6-month therapy (27.3%, n = 66; median cycles [range] = 12 [9][10][11][12]) or 3-month therapy (36.0%, n = 87; median cycles [range] = 6 [4][5][6][7]), and 89 patients (36.7%) were treated with surgery alone. Baseline patients and tumor characteristics between treatment durations were presented in Table 1.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…MSI is a consequence of a deficient mismatch repair (dMMR) system that results in error accumulation within microsatellite region, and it occurs in approximately 15% of all colorectal cancers (10). Several studies have shown that dMMR non-metastatic CC patients were associated with a more favorable stage-adjusted prognosis compared to patients with proficient mismatch repair (pMMR) (11)(12)(13)(14). Whether a shorter duration of adjuvant therapy for patients with dMMR would lead to any decrease in efficacy is still unclear.…”
Section: Introductionmentioning
confidence: 99%